2011
DOI: 10.1016/j.chom.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of a Plant Resistance Protein TIR Domain Reveals Interfaces for Self-Association, Signaling, and Autoregulation

Abstract: SUMMARY The Toll/interleukin-1 receptor (TIR) domain occurs in animal and plant immune receptors. In the animal Toll-like receptors, homodimerization of the intracellular TIR domain is required for initiation of signaling cascades leading to innate immunity. By contrast, the role of the TIR domain in cytoplasmic nucleotide-binding/leucine-rich repeat (NB-LRR) plant immune resistance proteins is poorly understood. L6 is a TIR-NB-LRR resistance protein from flax (Linum usitatissimum) that confers resistance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
400
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(425 citation statements)
references
References 64 publications
(87 reference statements)
20
400
0
5
Order By: Relevance
“…Many lines of evidence suggest TIR-TIR interactions are important for TNL function 24,37 . The TIR domains of RRS1 and RPS4 interact in a yeast two hybrid assay and associate in planta after co-IP 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Many lines of evidence suggest TIR-TIR interactions are important for TNL function 24,37 . The TIR domains of RRS1 and RPS4 interact in a yeast two hybrid assay and associate in planta after co-IP 24 .…”
Section: Resultsmentioning
confidence: 99%
“…The recent elucidation of the structures of the CC domain of MLA and the TIR domain of L6, a resistance protein against flax rust, both shown to form homodimers, has led to renewed attention for the role of self-association in the functioning of R proteins (Bernoux et al, 2011;Maekawa et al, 2011a). Multimerization via the NB-ARC domain after activation is a common theme in proteins belonging to the STAND clade (Danot et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…7C, 5). In case of Rx1, it was shown that the NB domain itself can initiate a cell death response in the absence of the other domains (Rairdan et al, 2008), but for several other NB-LRR R proteins, the Nterminal CC or TIR domain has signaling capabilities (Swiderski et al, 2009;Bernoux et al, 2011;Collier et al, 2011;Maekawa et al, 2011a). The electrostatic attraction between the conserved clusters of charged residues on the ARC2 and LRR is predicted to facilitate the reassociation of the domains when the R protein completes the activation cycle and returns to its resting state (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the N-terminal regions from several TIR-NB-LRRs has been previously reported to induce cell death (Frost et al, 2004;Weaver et al, 2006;Swiderski et al, 2009;Krasileva et al, 2010;Bernoux et al, 2011), suggesting that TIR domains are involved in defense signaling. We have reported that the N-terminal CC R domains of NRG1 and ADR1 also induce cell death (Collier et al, 2011).…”
Section: Discussion Activation Of Cell Death By the CC Domains Of I2-mentioning
confidence: 99%
“…In many cases, recognition of pathogens is mediated through plant recognition co-factors that interact both with the N-terminal TIR or CC domain of an NB-LRR and the cognate effector protein (Collier and Moffett, 2009;Saunders et al, 2012;Lewis et al, 2013). Expression of the N-terminal domains of some NB-LRRs has also been shown to induce cell death, including TIR (Frost et al, 2004;Weaver et al, 2006;Swiderski et al, 2009;Krasileva et al, 2010;Bernoux et al, 2011), CC (Maekawa et al, 2011;Wang et al, 2015), and CC R (Collier et al, 2011) domains. These observations have led to the question of whether the N termini of NB-LRR proteins are involved in pathogen recognition, signaling, or both.…”
mentioning
confidence: 99%